Neutron capture cross sections of 69Ga and 71Ga at 25 keV and e peak = 90 keV - Göbel, Kathrin (2017)
This project was supported by EFNUDAT, ERINDA, the EuroGENESIS project MASCHE, HIC for FAIR and BMBF (05P15RFFN1).